Effect of Induced-Moult on the Number Small Ovarian Follicles and Egg Production of Old Layers - Oguike, M.A.; Igboeli, G.; Ibe, S.N. (International Journal of Poultry Science, 2006)
Influence of induced-moult on small ovarian follicles and egg production of old laying flock was investigated. Small follicles were graded thus: small yellow follicles (SYF), large white follicles (LWF) and small white follicles (SWF). A total of 360 old layers in their 64 weeks in lay were used in a 2x3 factorial arrangement in a Completely Randomized Design (CRD). The induced-moult treatments were natural day length with feed and water ad libitum, natural day length with water but no feed, natural day length with no feed and no water, reduced day length with feed and water ad libitum, reduced day length with water but no feed, reduced day length with no feed and no water, represented as T1, T2, T3, T4, T5 and T6, respectively. Each treatment was replicated 3 times with 20 hens per replicate. At the commencement of the experiment the numbers of the small follicles of the Control (T1) were 7.67 ± 0.88, 18.33 ± 0.88, 2121.67 ± 5.78, for small yellow, large white and small white follicles, respectively. The results showed that with the exception of T4, the numbers of all the small follicles of the rest of the induced-moult groups were significantly decreased (P< 0.05) by day 7 of moult induction. The numbers of the small follicles of T2, T3, T5 and T6 gradually increased and became Significantly higher (P< 0.05) than the control (T1) by day 49 of moult induction. By day 49, the numbers of the small follicles of the induced-moult hens ranged from 2500± 17.56 to 3670.00± 4.05 (SWF), 24.33±0.88 to 41.00± 0.58 (LWF) and 5.00± 0.58 to 6.67± 0.20 (SYF). The mean egg production of the flock was about 50 % prior to moult induction. The hen-day percent production of the moult groups ranged from 50 to 79 % whereas that of the unmoulted control ranged from 35 to 55 %. In conclusion, moulting initiated regeneration and rejuvenation of follicles. This in turn led to increase in post moult egg production of the induced-moult groups.